Study on the matching scheme between early warning information dissemination demands and communication network dissemination channels - Jingli WANG; Yu ZHAO (Dianxin kexue)
Early warning information dissemination capacity is insufficient in timeliness, accuracy and wide coverage compared with the national emergency management system requirements.The dissemination demands were analyzed from early warning information receivers, emergency degree, receiving area and other factors.The early warning information transmission channels were extended to including cell broadcasting, Tiantong satellite and other communication networks.Then these channels were compared in the aspects of timeliness, accuracy, coverage and cost.For emergency responders and the public, according to typical scenarios, the matching scheme of early warning information communication channel selection was proposed, which laid a foundation for the optimization of communication channel.